Students’ Perspectives on Translanguaging Practices in English History Classes at a Private University, Bangladesh - Rahman, Md. Mahadi (The Outlook: Journal of English Studies, 2025)
This action research study investigates the effectiveness of translanguaging practices in an English History course at the Department of English Language and Literature, a Private University, Chattogram, Bangladesh. In this context, departmental policy requires an instruction to be conducted in English, despite students being the beginner-level English language learners. This creates significant challenges for the content comprehension, especially in history classes where the complex concepts and unfamiliar vocabulary are prevalent. The study employed qualitative methods to examine how the strategic use of Bengali (L1) alongside English (L2) affects students' understanding of historical content and their engagement in class. Data were collected through the semi-structured interviews with 13 undergraduate students and the systematic classroom observations over one semester. The findings reveal that the judicious use of translanguaging practices significantly enhanced students' comprehension of historical concepts, boosted their confidence in participating in class discussions, and reduced the anxiety related to content learning. Specifically, students demonstrated improved retention of historical events and concepts when explanations were scaffolded using their mother tongue. The research also identified effective translanguaging strategies, including the concept explanation in L1 after English introduction, clarification of complex historical terminology through the L1 equivalents, and encouragement of initial responses in L1 before transitioning to L2. These findings contribute to the growing body of literature on translanguaging pedagogy in the South Asian higher education contexts and challenge the monolingual approaches to the content teaching in the multilingual settings. The study concludes with practical recommendations for instructors teaching the content courses to ESL learners and suggests that the institutional language policies should be flexible enough to accommodate pedagogically sound translanguaging practices that prioritize the content comprehension while still promoting the target language development.